Twitter in the News: An Analysis of Embedded Tweets in Political News Coverage. Issue 9 (21st October 2022) - Oschatz, Corinna; Stier, Sebastian; Maier, Jürgen
Abstract: This study examines the growing journalistic practice of embedding full tweets in online political news coverage. Against the background of a hybrid media system, we pursue three research goals. First, we evaluate the scope of the Twitter-in-the-news phenomenon relative to news coverage as a whole. Second, we examine the functions of embedded tweets. Third, we identify characteristics that increase the likelihood that tweets will be selected for publication in a news article. We combine computational methods with a manual content analysis and analyze political news coverage of one month outside election periods in four German online news outlets. Our results show that embedding tweets in the news is not a niche phenomenon but has been established as a routine journalistic practice to a moderate extent. In the majority of news articles, the function of tweets is to illustrate an argument or information provided in the text. Geographical proximity and – with some dependencies – the number of popularity cues increased the likelihood of a tweet to be picked up for reporting. The paper shows how transformation processes currently observed in journalism manifest themselves in reporting.